Aluminum-silicon hydride clusters for prospective hydrogen storage. (8th October 2019) - Ma, Li; Zhou, Tao; Li, Jinyun; Chen, Hongshan
Abstract: The structures and bonding properties of Al4 Si2 H2n (n = 0–10) clusters are systematically studied by using the evolutionary algorithm combined with ab initio computations. While the H atoms are bond on the terminal sites of the clusters at low H contents, the Al atoms are combined together by double H-bridges and the Al/Si atoms are tetrahedrally coordinated at high H contents. The Al4 Si2 H2n clusters break into a few fragments for n = 9, 10. Analysis on the bonding natures shows that the Al–H bonds are strongly polarized and the Si atoms balance the charge states of the Al/H atoms according to the hydrogen concentrations. The hydrogen storage capacity in Al4 Si2 H16 cluster reaches 8.9 wt%, and the estimated strength of the hydrogen bonding is about −0.55 eV per H2, which falls in the ideal window for reversible hydrogen storage at ambient temperatures. The high hydrogen capacity and moderate bonding strength suggest that Al–Si hydrides can be promising candidates for hydrogen storage. Highlights: Structures and bonding properties of Al4 Si2 H2n (n = 0–10) are studied. Al atoms are bound by double H-bridges and Al/Si are tetrahedrally coordinated. Al–H bonds are strongly polarized and Si atoms balance the charge states. The hydrogen bonding strength is about −0.55 eV per H2 . Hydrogen storage capacity in Al4 Si2 H16 reaches 8.9 wt%.